2019
DOI: 10.35444/ijana.2019.11036
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Detection: Feature Extraction & SVM Classification

Abstract: Oral or mouth neoplasm is the type of head & neck cancers. This type of cancer starts in the throat or mouth due to uncontrollable growth of tissues, and it looks like a lump or bump. In the pre-processing step, anisotropic diffusion filter used to filter unwanted distortions from MRI image. Next, the lesion separated from MRI image using a hybrid approach KFCM clustering in segmentation and features extracted using Intensity of Histogram, GLCM & GLRLM. The comparison between these three algorithms is performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Shilpa Harnale et al [45] suggested the Support Vector Machine classifier for oral cancer detection. An effective algorithm for detecting lesions in the early phases and achieving high precision is the Hybrid Approach to KFCM segmentation.…”
Section: Related Workmentioning
confidence: 99%
“…Shilpa Harnale et al [45] suggested the Support Vector Machine classifier for oral cancer detection. An effective algorithm for detecting lesions in the early phases and achieving high precision is the Hybrid Approach to KFCM segmentation.…”
Section: Related Workmentioning
confidence: 99%
“…Performance metrics, including accuracy, sensitivity [15], and specificity, exhibit commendable levels, suggesting the effectiveness of the combined ResNet18-SVM methodology. Comparative analyses against existing methods underscore the potential of our approach in facilitating early and accurate oral cancer diagnosis [7,9]. The implications of automated oral cancer detection are far-reaching, with the potential to revolutionize clinical practices by enabling prompt interventions and improving patient prognosis.…”
mentioning
confidence: 99%